2022
DOI: 10.1111/josi.12544
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of societal ageism and declines in subjective memory during the COVID‐19 pandemic: Longitudinal evidence from US adults aged ≥55 years

Abstract: The cognitive health of older adults since the COVID‐19 pandemic onset is unclear, as is the potential impact of pandemic‐associated societal ageism on perceived cognition. We investigated associations between perceptions of societal ageism and changes in subjective memory over a 10‐month period during the COVID‐19 pandemic. We collected longitudinal data from monthly online questionnaires in the nationwide COVID‐19 Coping Study of US adults aged ≥55 from April 2020 to January 2021 (N = 4444). We analyzed the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 75 publications
0
13
1
Order By: Relevance
“…Although not evident in our data, there is the risk that benevolent ageism might foster cognitive decline (Cohn-Schwartz et al, 2022;Sublett & Bisconti, 2020; see also Giebel et al, 2021, with respect to dementia). Additionally, the policies restricted individual autonomy, challenged established ways of communication, and consequently, increased anxiety.…”
Section: Discussioncontrasting
confidence: 56%
“…Although not evident in our data, there is the risk that benevolent ageism might foster cognitive decline (Cohn-Schwartz et al, 2022;Sublett & Bisconti, 2020; see also Giebel et al, 2021, with respect to dementia). Additionally, the policies restricted individual autonomy, challenged established ways of communication, and consequently, increased anxiety.…”
Section: Discussioncontrasting
confidence: 56%
“…Ageism toward older adults—or negative age‐based stereotypes, prejudice, and discrimination enacted toward older adults (Butler, 1969 )—is a widely studied (Nelson, 2016 ), pervasive social problem, with pernicious effects on the mental health (Bai et al., 2016 ; Chrisler et al., 2016 ; Lyons et al., 2018 ), cognitive health (Cohn‐Schwartz et al., 2022 ), physical functioning (Allen, 2016 ), and overall wellbeing (Kim & Jung, 2021 ; Sabik, 2015 ) of older adults. Concern about the ramifications of ageism toward older adults heightened in March of 2020 at the onset of the COVID‐19 pandemic (Swift & Chasteen, 2021 ), as public health messaging stressed the significant risks of the virus to older adults with medical comorbidities (Morrow‐Howell et al., 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are at higher risk from COVID-19, with greater disease severity and higher mortality compared to younger people (Cerasoli, 2020). Recent research highlights that the COVID-19 health and safety measures have led to increased mental health problems, such as increased feelings of depression, anxiety, social isolation, and loneliness, potentially cognitive decline (Allen et al 2021;Bailey et al, 2021;Dahlberg, 2021;Derrer-Merk et al, 2022b;Derrer-Merk et al, 2022a;Heidinger & Richter, 2020;Richter & Heidinger, 2021;Krendl & Perry, 2021;Litwin & Levinsky, 2021;De Pue et al 2021;Shahid et al, 2020;Smith et al, 2020;Cohn-Schwartz et al, 2022;Tsoukalis-Chaikalis et al, 2021;van Gerwen et al, 2021;Victor et al, 2022;Vrach &Tomar, 2020). Other studies reported the consequences of age discrimination (Derrer-Merk et al, 2022c;Lytle & Levy, 2022;MCDarby, 2022;Drury et al, 2022;Kanik et al, 2022;Spaccatini et al, 2022;Sutter et al, 2022;Swift & Chasteen, 2021;).…”
Section: Introductionmentioning
confidence: 99%